Complete mitochondrial genome organization of Tor tor (Hamilton, 1822). (3rd July 2016) - Kumar, Rohit; Goel, Chirag; Kumari Sahoo, Prabhati; Singh, Atul K; Barat, Ashoktaru
Abstract: The complete mitochondrial genome of Tor tor, a threatened "Mahseer" was sequenced for the first time. The mitochondrial genome size determined to be 16, 554 bp in length and consisted of 13 protein-coding genes (PCGs), 22 tRNAs, 2 rRNA genes and a control region or displacement loop (D-Loop) region, resembling the typical organizational pattern of most of the teleost. The overall base composition found was A: 31.8%, T: 25%, G: 15.7% and C: 27.4%; A + T: 56.9% and G + C: 43.1%. The phylogenetic tree constructed using 11 other cyprinids' total mtDNA datasets confirmed the location of present species among mahseers. The total sequence data could support further study in molecular systematics, species identification, evolutionary and conservation genetics.